Peran Orang Tua dan Guru dalam Mencegah Berita “ Hoax ” Pada Siswa SMP - Maria Cleopatra; Sara Sahrazad; Lusiana Wulansari (Jurnal Ilmiah Wahana Pendidikan, 2020)
The use of computers and devices (mobile phones), is very important in life. The tool has become part of life. However, haphazard usage and do not have enough knowledge in its use, will be a problem. This study aims to describe the role of parents and teachers in preventing lies among junior high school students. The study was conducted for 3 months. The method used is a qualitative method. 25 respondents, consisting of 10 parents and 15 junior high school teachers. The results showed that there was still a lack of parental supervision regarding the use of devices. Parents have not been maximized to provide rules and knowledge of good device use, and it is feared that students will not filter incoming information. The teachers have monitored the use of devices, and have socialized the use of devices. This needs to be improved.